Pengaruh Pendidikan Kesehatan terhadap Pengetahuan Kesehatan Gigi pada Anak Usia Sekolah di SD Islam Al-Falah Jambi - Suri, Marta; Alfajri, Jufri; Putri, Vevi Suryenti (Jurnal Akademika Baiturrahim Jambi, 2025)
Dental caries is an infectious disease that damages the tooth structure and causes cavities. This study was conducted at SD Islam Al-Falah Jambi on August 22, 2022, with the aim of determining the impact of health education on dental health knowledge among school children. The research used a quantitative method with a pre-experimental design, specifically a one-group pre-test and post-test. The sample consisted of 20 children selected through random sampling. The instrument used was a questionnaire, and the data were analyzed using univariate and bivariate analysis, with the Wilcoxon Signed Ranks Test. The results showed that the average knowledge score of the respondents before the health education was 10.55, and after the health education, the average knowledge score increased to 13.10, with a difference of 2.55. This indicates that the average knowledge of the respondents before the health education was lower than after. There was a significant effect of health education on the dental health knowledge of school-aged children at SD Islam Al-Falah Jambi (p = 0.000). SD Islam Al-Falah Jambi is expected to strengthen its School Health Unit (UKS) programs related to dental health by organizing regular dental health education sessions. The school is also encouraged to implement a routine dental check-up program in collaboration with the local health center (Puskesmas) to ensure the students' dental health is monitored optimally.